Factors affecting biopore-root interaction: a review - Md. Dhin Islam; Bushra Islam Binte; Yehia Hazzazi; Mohammed Zia Uddin Kamal (Discover Agriculture, 2024)
Abstract Biopores formed by the actions of decaying roots of plants and soil fauna are essential for providing preferential growth pathways into deeper soil when the subsoil is compacted. Biopores help with rapid transportation of oxygen which increases microbial activity. These positive impacts help to increase the yield of crops even in adverse environmental conditions. However, the impact of biopores depends on various climatic and soil conditions. Understanding the mechanisms of different factors controlling the influences of biopores on the growth and development of plant roots is essential for getting more benefits in crop production. While several reviews have explored biopore-root interactions in crop production, there remains a lack of systematic studies on the factors influencing these interactions. In this review, we discussed different factors affecting the impacts of biopores on various crops in different situations based on current literature. It is also explained how we can maximize these impacts for getting benefits in sustainable crop production. Biopore improves the soil structure which has vital role on the growth of crops. On the other hand, clumping of roots within the biopores was also observed which may negatively affect crop growth. Similarly, biopores increase water infiltration as well as the leaching of nutrients. The influences of biopores depend on pore characteristics, abundance of biopores, moisture content, management practices, edaphic conditions, plant species etc. Understanding the factors influencing biopore-root interaction can contribute to improve root accessing into the deeper soil, enhancing their adaptation in stressful soil conditions.